Integrative anatomical and two-dimensional ultrasonographic assessment of the heart in Shetland ponies - Matos, Jorge Isidoro; Pitti, Lidia; Parra-Quijano, María; Arencibia, Alberto; Ramírez, Gregorio; Díaz-Bertrana, María Luisa (Frontiers in Veterinary Science, 2026)
ObjectiveThe purpose of this study was to characterize the normal anatomy of the Shetland pony heart through an integrative approach combining two-dimensional transthoracic echocardiography and anatomical dissection.MethodsTransthoracic echocardiographic examinations were performed in 19 clinically healthy Shetland ponies, obtaining standardized longitudinal and cross-sectional two-dimensional views of the heart. These images were used to describe the main echocardiographic windows and to document the visualization of relevant cardiac structures. In parallel, four Shetland pony hearts were dissected and sectioned, allowing an illustrative correspondence between anatomical landmarks and representative echocardiographic views, thereby facilitating a more precise interpretation of the observed structures. Furthermore, basic two-dimensional echocardiographic measurements were determined, including diameters of key cardiovascular chambers and vessels.ResultsNineteen Shetland ponies (median age 6.8 years; median body weight 136.9 kg) were evaluated. Anatomical analysis allowed identification of the main cardiac structures and their topographic relationships, which showed illustrative correspondence with the two-dimensional echocardiographic views. The largest measurements were the left ventricular diastolic diameter (5.4 cm) and the left atrial diastolic diameter (4.2 cm), while the smallest was the right ventricular free wall in diastole (1.2 cm). Intra-observer variability was low (ICC = 0.94; CV = 3.2%), confirming high measurement repeatability.ConclusionOverall, the data obtained provide an adequate anatomical reference and offer relevant insights to support the interpretation of transthoracic two-dimensional echocardiographic studies in Shetland ponies.